Moral responsibility and speaking to the 'dark side of human rights' - Becker, A. (South African Journal of Higher Education, 2017)
This article uses a postmodern lens to question assumptions inherent to three normative claims for the human rights project in the context of post-1994 South Africa. The claims are that human rights are part of humanity’s narrative of progress; that they are universal and inclusive; and that their subject is the liberal humanist subject. Kapur (2006) argues that these claims paradoxically point to the ‘dark side of human rights’. By plugging data into theory and theory into data (Jackson & Mazzei 2012). I argue that student-teachers engage with human rights in a discursive manner and structure relations between self and the Other in rational human rights spaces. I pose that by choosing responsibility for an Other[i], South Africans can transcend rational spaces and structure relations between self and an Other in moral spaces. In moral spaces the conflict inherent to the contradictory nature of moral choices and the conflict between self-consciousness and renunciation present possibilities for continually re-structuring human rights and a humane world (cf. Fanon,1967). [i] In reference to Booth (1999) I use the Other and an Other alternatively to indicate the nature of the relation between self and Other. The Other refers to a relation of distance. An Other refers to a relation of proximity in which self faces an Other and responds accordingly.